A study on effectiveness of training program toward employees in Tabung Haji / Nurul Faraha Suwany Ahmad - Ahmad, Nurul Faraha Suwany (2012)
This thesis present a study which has sought to the effectiveness of training program in Tabung Haji and at the same time identifies the purpose of training program toward employees. Besides that, this thesis is about to identifying the factors which is knowledge, skills and attitude that contribute to the effectiveness of training program toward employee. Training program are the most important role in enhancing and increasing the employees performances and organization productivity. Through training also we can see either there has a level of improvement in employees performance. It is noteworthy to investigate how the factors contribute to the effectiveness of training program toward employee. A survey was conducted through distribute of questionnaire to the employee that who attend the training program from different background profile of Tabung Haji. In this research it just focuses on 34 respondents that attend the Emergency Response Plan and Preparedness training program only and administered questionnaire were distribute and collected simultaneously, which have resulted 100% rate. Using statistical Package for Social Science (SPSS) , the data was computed and analyzes based on the effectiveness of training program. The result is in form frequency, reliability and correlation. The result indicate that, there are significant relationship between all the factors which is knowledge, skills and attitude with the effectiveness of training program toward employee in Tabung Haji.